COMPREHENSIVE CLINICAL INTERVENTIONS FOR THE PREVENTION AND MANAGEMENT OF DENTURE-RELATED ORAL MUCOSAL DISORDERS - Rasulova Mokhigul Matyokub kizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. Removable dentures are a key etiological factor in oral mucosal disorders, particularly prosthetic stomatitis. Mechanical irritation, oral microbiota imbalance, and local immune disruption contribute to inflammation, often presenting with mild or subclinical symptoms that delay diagnosis. Modern therapeutic approaches focus on promoting epithelial repair, stabilizing intraoral pH, reducing hyperemia and discomfort, and improving patient adherence. Clinical evidence suggests that innovative treatment strategies may surpass conventional regimens in efficacy. Additionally, sensitive non-invasive biomarkers can support early detection and better prognostic outcomes in denture-associated mucosal pathology.